A comprehensive analysis and validation of cuproptosis-associated genes across cancers: Overall survival, the tumor microenvironment, stemness scores, and drug sensitivity - Liu, Jinsong; Lu, Yueyao; Dai, Yuyang; Shen, Ying; Zeng, Cheng; Liu, Xiuling; Yu, Huayi; Deng, Jianzhong; Lu, Wenbin (Frontiers in Genetics, 2022)
Background: Cuproptosis is a novel type of cell death induced by copper. Cuproptosis-associated genes play a crucial part in oncogenesis and the growth and metastasis of tumors. However, the correlations among cuproptosis-associated genes, overall survival, the tumor microenvironment, and drug sensitivity remain unclear. Therefore, we performed an analysis of cuproptosis-associated genes across cancers. Methods: We downloaded RNA sequence expression data, clinical and survival data, stemness score data, and immune subtype data of cuproptosis-associated genes from the UCSC Xena. Next, we conducted differential analysis, expression analysis and correlation analysis across cancers with various R packages. Moreover, survival analysis and Cox hazard analysis were conducted to investigate the relationships between cuproptosis-associated genes and survival outcomes in various cancer types. Finally, we also analyzed the relationship among the levels of cuproptosis-associated genes across cancers, immune types, the tumor microenvironment, stemness scores, and drug sensitivity. Expression validation of cuproptosis-associated genes in renal cancer and normal tissues by immunohistochemical staining. Results: We found that 10 cuproptosis-associated genes (FDX1, LIAS, LIPT1, DLD, DLAT, PDHA1, PDHB, MTF1, GLS, and CDKN2A) were differently expressed in 18 tumors and normal tissues. Survival outcomes showed that cuproptosis-associated genes had prognostic value in various cancer types. Moreover, we identified that cuproptosis-associated genes had different levels in six immune subtypes. The study also indicated that the levels of most cuproptosis-associated genes were positively correlated with the RNAss and DNAss. FDX1, LIAS, LIPT1, DLD, DLAT, PDHA1, and PDHB were negatively correlated with immune scores and ESTIMATE scores. In addition, we identified the top 16 drugs strongly sensitivity to cuproptosis-associated genes according to the correlation coefficient. Finally, we also found that cuproptosis-associated genes were significantly correlated with immune subtype, clinical features, the tumor microenvironment, and drug sensitivity in Kidney renal clear cell carcinoma. And the results of immunohistochemical staining analysis was very consistent with the previous analysis. Conclusion: We performed an overall analysis to uncover the roles of cuproptosis-associated genes in differential expression, survival outcomes, immune subtypes, the tumor microenvironment, stemness scores, and cancer drug sensitivity across cancers.